(untitled) - Misra, Devandra K. (Hoboken, 2007)
Learn to solve both simple and complex electromagnetic problems with this text's unique integration of theoretical and mathematical concepts. With the author’s guidance, you’ll discover a broad range of classic and cutting-edge applications across a wide array of fields, including biomedicine, wireless communication, process control, and instrumentation. Case studies, detailed derivations, and 170 fully solved examples deepen your understanding of theory, and help you apply numerical methods to real-world problems.
Keywords: Electromagnetism; United States